Mechanical activation influence on the morphological properties of La[2]O[3]-TiO[2]-B; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Dolmatov O. Yu. Oleg Yurevich; Zakusilov V. V. Vladislav Vladimirovich; Kuznetsov M. S. Mikhail Sergeyevich; Pimenov N.; Chursin S. S. Stanislav Sergeevich (Materials Science in Mechanical Engineering, 2016)
Title screen